Embed Code - If you would like this activity on your web page, copy the script below and paste it into your web page.

Normal Size Small Size show me how

Normal Size Small Size show me how

# Module 6: Math 113

### Module 6: Solving Systems of Linear Equations by Addition and in Three Variables

Question | Answer |
---|---|

1. Solve the system for x = {x+y=4 {x-y=8 | First, eliminate the y variable by adding the equations together. Making the equation 2x=12. Devide both sides by 2 to eliminate 2x. Answer is: x = 12 |

Solve the system for y = {x+y=4 {12+y=4 | Now you know x = 6 so plug it into one of the equations as the x-value. Solve for y. y = 4 - 12. making the answer y = -8. The solution for the system is (8,4) |

2. Solve the system = {-2x+y=2 {-x-3y=4 | Multiply both sides of the first equation by 3. Making the equation -3(-2x+y)= -3(2). Simplifies to 6x-3y=-6 |

Solve for; {6x-3y=-6 {-x-3x=y | Add the resulting eqations and divide by 5, giving you the answer x = -2 |

Solve for Y = {-2 + y = 2 | Plug in -2 for x. Making the equation -2(-2)+y=2. Giving you 4+y=2. Subtract 4 from both sides. Your answer is y=-2 |

When do you multiply both sides by a chosen number? | EVERY time when solving by the addition method. |

Solving for true statements. {3x-2y=2 {-9x+6y=-6 | Multiply both sides of the first equation by 3, giving you {3(3x-2y)=3(2). Simplify and add both equations. Anser becomes 0=0, a TRUE statement. |

Solving systems of two linear equations by the addition method. Solve this system; -x - y/2 =5/2 - x/2+y/4 = 0 | First we multiply both equations by their lowest common denominator which, in this case, is 2 and 4. making them {-2x-y=5 {-2x+y=0 |

Now finish solving {-2x-y=5 {-2x+y=0 | add the equations to get -4x=5. |

Sove for Y from the previous equation. | Solve by eliminating X. To do this, Multiply each side of the first equation by -1. to make it {-1(-2x-y)=-1(5). simplify then add the two equations. your answer is y= -5/2 |

Solve the System = {3x-y+z=-15 {x+2y-z=1 {2x+3y-2z=0 | Add equations 1 and 2 to eliminate Z and create equation 4.Use 1 and 3 to eliminate Z again by multilpying both sides of equation one by 2.Add this to equation 3 to get equation 5. Now multiply both sides of equation 4 by -1 simplify and add to equation 5 |

Solve the System = {2x-4t+8z=2 {-x-3y+z=11 {x-2y+4z=0 | Add 1 & 2 to eliminate Z and get eq 4. Add 1 & 3 to eliminate Z again and get eq 5. Add 4 & 5 to solve for X & Y. |

Solve the system; {6x-3y+12z=4 {-6x+4y-2z=7 {-2x+y-4z=3 | Add 1 & 2 to eliminate Z and get eq 4. Add 1 & 3 to eliminate Z again and get eq 5. Add 4 & 5 to solve for X & Y. |

Created by:
1012127019